Maternal Pre-conception Body Mass Index and Fasting Plasma Glucose With the Risk of Pre-term Birth: A Cohort Study Including 4.9 Million Chinese Women - Xu, Qin; Zhou, Qiongjie; Yang, Ying; Liu, Fangchao; Wang, Long; Wang, Qiaomei; Shen, Haiping; Xu, Zongyu; Zhang, Yiping; Yan, Donghai; Peng, Zuoqi; He, Yuan; et al. (Frontiers in Reproductive Health, 2021)
Background: To evaluate the associations of pre-conception body mass index (BMI), fasting plasma glucose (FPG) alone and their combination with pre-term birth (PTB) risk. Methods: We conducted a population-based retrospective cohort study with 4,987,129 reproductive-aged women, who participated in National Free Pre-Pregnancy Checkups Project in 2013–2016 and had a singleton delivery before December 2017 in China. All data analyses were conducted in 2018–2021. Results: A total of 339,662 (6.81%) women had pre-term deliveries. Compared with women with normal weight and normal glucose, underweight and normal weight were associated with PTB among hypoglycemia women, the adjusted odd ratios (aORs) were 1.24 (95% CI: 1.05–1.48) and 1.16 (95% CI: 1.07–1.25), respectively; underweight, overweight and obesity were associated with PTB among women with normal glucose, the aORs were 1.09 (95% CI: 1.08–1.10), 1.06 (95% CI: 1.05–1.07) and 1.08 (95% CI: 1.05–1.12), respectively; all the BMI groups were significantly associated with PTB among women with pre-diabetes or diabetes (P < 0.05). The dose-response relationships of BMI with PTB varied in different FPG level, with U-shaped curve in normal glucose and pre-diabetes women, J-shaped in diabetes women, L-shaped in hypoglycemia women. For FPG with PTB, the dose-response relationships were U-shaped in normal weight, overweight, and obesity women, and L-shaped in underweight women. Conclusion: We found that the associations of PTB with BMI varied with levels of FPG, and associations of PTB with FPG varied with levels of BMI. There was a synergistic effect on PTB risk due to abnormal weight and glycemia besides a conventional main effect derived from either of them. Achieving desirable weight and glucose control before conception should be advised.